Hybrid Ensemble Pruning Using Coevolution Binary Glowworm Swarm Optimization and Reduce-Error. (31st October 2020) - Zhu, Xuhui; Ni, Zhiwei; Xia, Pingfan; Ni, Liping
Abstract : Ensemble pruning has been widely applied to improve the capacity of multiple learner system. Both diversity and classification accuracy of learners are considered as two key factors for achieving an ensemble with competitive classification ability. Considering that extreme learning machine (ELM) is characterized by excellent training rate and generalization capability, it is employed as the base classifier. For a multiple ELM system, when we increase its constituents' diversity, the mean accuracy of the whole members must be decreased. Therefore, a compromise between them can ensure that the ELMs remain good diversity and high precision, but finding the compromise brings a heavy computational burden. It is hard to look for the exact result via the searching of intelligent algorithms or pruning of diversity measures. On the basis, we propose a hybrid ensemble pruning approach employing coevolution binary glowworm swarm optimization and reduce-error (HEPCBR). Considering the good performance of reduce-error (RE) in selecting ELMs with high diversity and precision, we try to employ RE to choose the satisfactory ELMs from the generated ELMs. In addition, the constituents are further selected via the proposed coevolution binary glowworm swarm optimization, which are utilized to construct the promising ensemble. Experimental results indicate that, compared to other frequently used methods, the proposed HEPCBR achieves significantly superior performance in classification.